T lymphocytes and normal tissue responses to radiation - Schaue, Dörthe; McBride, William H. (Frontiers in Oncology, 2012)
There is compelling evidence that lymphocytes are a recurring feature in radiation damaged normal tissues, but assessing their functional significance has proven difficult. Contradictory roles have been postulated in both tissue pathogenesis and protection, although these are not necessarily mutually exclusive as the immune system can display what may seem to be opposing faces at any one time. While the exact role of T lymphocytes in irradiated normal tissue responses may still be obscure, their accumulation after tissue damage suggests they may be critical targets for radiotherapeutic intervention and worthy of further study. This is accentuated by recent findings that pathologically damaged “self”, such as occurs after exposure to ionizing radiation, can generate danger signals with the ability to activate pathways similar to those that activate adoptive immunity to pathogens. In addition, the demonstration of T cell subsets with their recognition radars tuned to “self” moieties has revolutionized our ideas on how all immune responses are controlled and regulated. New concepts of autoimmunity have resulted based on the dissociation of immune functions between different subsets of immune cells. It is becoming axiomatic that the immune system has the power to regulate radiation-induced tissue damage, from failure of regeneration to fibrosis, to acute and chronic late effects, and even to carcinogenesis. Our understanding of the interplay between T lymphocytes and radiation-damaged tissue may still be rudimentary but this is a good time to reexamine their potential roles, their radiobiological and microenvironmental influences, and the possibilities for therapeutic manipulation. This review will discuss the yin and yang of T cell responses within the context of radiation exposures, how they might drive or protect against normal tissue side effects and what we may be able do about it.